Macroeconomic Effects of Public Pension Reforms - Pereira, Joana (IMF Working Papers; Working Paper ;, 2010)
The paper explores the macroeconomic effects of three public pension reforms, namely an increase in retirement age, a reduction in benefits and an increase in contribution rates. Using a five-region version of the IMF's Global Integrated Monetary and Fiscal model (GIMF), we find that public pension reforms can have a positive effect on growth in both the short run, propelled by rising consumption, and in the long run, due to lower government debt crowding in higher investment. We also find that a reform action undertaken cooperatively by all regions results in larger output effects, reflecting stronger capital accumulation due to higher world savings. An increase in the retirement age reform yields the strongest impact in the short run, due to the demand effects of higher labor income and in the long run because of supply effects.